Pro-Tanto Obligations and Ceteris-Paribus Rules - Frederick, Danny (Journal of moral philosophy, 2015)
I summarize a conception of morality as containing a set of rules which hold ceteris paribus and which impose pro-tanto obligations. I explain two ways in which moral rules are ceteris-paribus, according to whether an exception is duty-voiding or duty-overriding. I defend the claim that moral rules are ceteris-paribus against two qualms suggested by Luke Robinson’s discussion of moral rules and against the worry that such rules are uninformative. I show that Robinson’s argument that moral rules cannot ground pro-tanto obligations is unsound, because it confuses an absolute reason for an obligation with a reason for an absolute obligation, and because it overlooks the possibility that priority rules may be rules for ordering pro-tanto obligations rather than rules for eliminating contenders for the status of absolute obligation.